Positive teacher feedback and adolescents’ reading self-efficacy: a quasi-experimental analysis using PISA 2018 - Xue Wang; Qiyang Zhang; Marcia H. Davis (Large-scale Assessments in Education)
Abstract Positive teacher feedback plays a crucial role in student learning. While previous studies on positive teacher feedback have primarily focused on its relationship with student achievement, much less attention has been given to how such feedback associates with student self-efficacy, particularly reading self-efficacy—a key predictor of both reading and overall academic success—among adolescents. The existing research that has explored this relationship often relied on small-sample, correlational studies, which often failed to account for a broad range of potential confounding variables. This study addresses these gaps by applying propensity score matching and weighting to a nationally representative sample of 4,838 U.S. adolescents from the Programme for International Student Assessment (PISA) 2018 data, controlling for an extensive set of covariates. The rationale for using propensity score matching and weighting was to reduce selection bias and better estimate the relationship between positive teacher feedback and student reading self-efficacy. Results show that positive teacher feedback is significantly associated with higher reading self-efficacy among adolescents, with stronger associations observed among students who receive it less frequently. This means increasing positive feedback could potentially benefit adolescents’ reading self-efficacy overall, but may be particularly beneficial for certain groups of students. This study highlights the potential value of teacher training programs focused on positive feedback to support students’ reading self-efficacy.